Medulla Spinalis’in Klinik Anatomisi - Yılmaz, Emre; Seçgin, Yusuf; Toy, Şeyma (Anatomiye Güncel Bakış II, 2024)
Bu bölümde medulla spinalis’in anatomisi ve klinik anatomisi hakkında detaylı bilgiler verilmektedir. Bölüm içerisinde medulla spinalis, spinal sinir kökleri, medulla spinalis’in kesitsel anatomisi, substantia grisea, substantia alba, medulla spinalis’in dolaşımı ve medulla spinalis’in klinik anatomisi yer almaktadır. This chapter provides detailed information about the anatomy and clinical anatomy of the medulla spinalis. The chapter includes the medulla spinalis, spinal nerve roots, cross-sectional anatomy of the medulla spinalis, substantia grisea, substantia alba, circulation of the medulla spinalis and clinical anatomy of the medulla spinalis.